OPTIMALISASI PENGENDALIAN HAMA TIKUS MELALUI PROGRAM BINA DESA DENGAN APLIKASI LETUPAN EMPOS TIKUS DI LAHAN BASAH - Muslimin Sepe; Wahyu Bimas Abadi; Jubaidah Jubaidah; Siti Maulydia Rahmah; Echa Aulia Listiaweni; Rizky Amelia Safitri; Jannatul Fatwa; M. Ridho Putra Perdana; Muhammad Fadhil Fitrian; Muhammad Husein Nafarin Aruba; Muhammad Farizh Faqih; Rachmad Guntur Saputra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2026)
The Rural Community Development program (Bina Desa) at Universitas Lambung Mangkurat is an implementation of the Integrated Learning Activity Mobility (MKBT) framework, an expansion of the Merdeka Belajar Kampus Merdeka (MBKM) policy. This program aims to facilitate cross-disciplinary and international learning experiences, bridging the gap between theoretical academic discourse and empirical field practice to enhance students' global competitiveness. This study details a community service initiative conducted in Astambul District, focusing on rodent pest management through the application of